Centralizing cohesion policy in times of austerity: evidence from the policy cycle. (4th July 2021) - Casula, Mattia
ABSTRACT: European policy-making has been interpreted as a pendulum that swings between the Member States (MSs) and the transnational arena when choices about where to assign policy responsibilities have to be made. As in other policy sectors, the pendulum metaphor has been used to interpret the changes which have occurred in Cohesion Policy supremacy. This article analyses how the attribution of responsibilities between the European Commission (EC), and the MSs has changed in the different phases of the policy cycle since the 1988 reform to the present day, simultaneously with the main stages of the European integration process. The main argument is that the 2008 Global Financial Crisis was a critical juncture within the history of the aforementioned integration process because it opened the way for the pursuit of new paths: it favoured the consolidation of a new governance system that pivots on the EC's active role, by identifying Cohesion Policy as the main instrument to pursue the Europe 2020 objectives. Accordingly, this article provides interpretative keys with which to explain the changes that have occurred in intergovernmental relations since the 1988 reform, as well as analytical tools with which to understand the ongoing debate on the future of EU policy-making.